Neglected Intestinal Parasites, Malnutrition and Associated Key Factors : A Population Based Cross-Sectional Study among Indigenous Communities in Sarawak, Malaysia - Yamuna, Rajoo; Stephen, Ambu; Yvonne Ai, Lian Lim; Komalaveni, Rajoo; Siew, Chang Tey; Chan, Woon Lu; Romano, Ngui (PLOS, 2017)
Intestinal parasitic infections (IPIs) have been recognized as one of the most significant causes of illness among disadvantaged communities. Many studies have been conducted on the prevalence of IPIs in Malaysia. However, these studies mostly focused on the indigenous groups in Peninsular Malaysia. The present study was conducted to provide the current baseline data on prevalence of IPIs, anaemia, malnutrition and associated risk factors among the indigenous communities in Sarawak, situation at northwest Borneo island of Malaysia. A cross sectional study was conducted among the longhouses communities. Stool samples were obtained and examined for the presence of IPIs using microscopy technique. Haemoglobin measurement was done using a portable haemoglobin analyzer. Malnutrition (i.e., stunting, underweight and wasting) was assessed using the WHO Anthro software. Statistical analysis was carried out using SPSS software. A total of 341participants took part in this study. The overall prevalence of IPIs was 57.5%. Multivariate analysis indicated that the absence of toilets (OR = 1.6; 95% CI = 1.1–2.7; p = 0.002) and close contact with animals (OR = 1.8; 95% CI = 1.3–2.9; p = 0.027) as significant predictors for IPIs. The incidence of anaemia was 36.4%. The incidence of underweight, wasting and stunting were 22.2%, 5.6% and 35.4%, respectively. Multivariate analysis demonstrated that low level of parental education attainment (OR = 1.9; 95% CI = 1.2–3.0; p = 0.006) was identified as significant predictor for anaemia. The incidence of wasting was significantly associated with mild anaemia (OR = 1.2; 95% CI = 0.9–1.7; p = 0.024). Low household income was identified as significant predictor for stunting (OR = 2.1; 95% CI = 9.8–22.2; p = 0.001) and underweight (OR = 1.9; 95% CI = 5.6–18.7; p = 0.037), respectively. Essentially, the present study highlighted that intestinal parasitic infections, anaemia and malnutrition are still prevalent among rural indigenous community in Sarawak. Improvement of socioeconomic status, periodic mass deworming, iron supplementation and health education program should be included in the control and prevention of public health strategies.